FeAl2O4 Thin Films Prepared by Sol-gel – Structural and Magnetic Properties. (2015) - Azam, M.; Nairan, Adeela; Riaz, Saira; Naseem, Shahzad
Abstract: Spinel ferrites are very important magnetic materials because of their interesting magnetic properties combined with their high chemical and thermal stability. Spinel ferrites have found wide applications in magnetic recording, sensors, photomagnetics, as heterogeneous catalysts, adsorption and humidity sensors, and oxygen sensors. Among the spinel ferrites FeAl2 O4 is given very little importance especially study of magnetic properties in thin films is given very little importance. We here report preparation of iron aluminum oxide (FeAl2 O4 ) thin films using sol-gel method. The ratio of Fe/Al is varied as 0.4, 0.5 and 0.6. Iron aluminum oxide phase is formed with Fe/Al ratio of 0.4 whereas high Fe/Al ratio results in formation of Fe2 O3 phase along with iron aluminum oxide. This phase purity leads to ferromagnetic properties of iron aluminum oxide thin films. Whereas weak ferromagnetic behavior at Fe/Al ratio of 0.5 and 0.6 is due to the presence of Fe2 O3 phase.